Zur Widerlegung von von Vavilos geographischer-botanischer Differentialmethode - Brücher, Heinz (ERDKUNDE, 1971)
A large number of mankind's most important domesticated plants originated in South America. Vavilov (1887-1943) established the theory that one could localise their genetic and geographical origin into a small number of centres. In these geographically tightly limited areas which, according to Vavilov, lay in isolated mountain regions, one could have encountered the wild original types with a large number of primitive agricultural peoples and cultivators. He called these areas 'gene centres'. For South America he postulated a 'gene centre' in the central Cordillera (Peru and Bolivia) and a further one on the island of Chiloe. Over several decades of research, the author has investigated these 'gene centres' and numerous South American domesticated plants and has been able to establish discrepancies between the Vavilov doctrine and the actual field situation. Thus there is, for example, absolutely no biological justification for calling the island of Chiloe a 'gene centre'. In contradiction of what Russian and other authors have asserted, it is not the case that the wild potatoes that occur there were the sort from which Solanus tuberosum could have developed. The existing diploid, triploid and tetraploid potatoes on Chiloe are relicts of Andean introductions. Using the example of the domesticated species Ananas, Arachis, and Phaseolus and their wild forms, the author shows that their origin, evolution and domestication did not take place in Vavilov's 'Gene Centre VIII'. Wild forms of pineapple occur in the riverine areas of the Paraguay and Parana south of the equator as well as on the Orinoco and Ventuari north of the equator. Venezuala is a plausible location for its domestication. There can be no question of a geographical link with 'Gene Centre VIII’. The wild forms of Arachis reach from the Atlantic coast of Brazil through the northern provinces of Argentina and Paraguay right to the base of the Cordillera in Bolivia. On the basis of cytogenetic and hybridological investigations, it is clear that Arachis hypogaea is an amphliploid and thus a locally limited area of origin, especially the Cordillera area, must be discounted. One of the genomes, in fact, comes from the Brazilian steppe form A. villosa. The domestication of the cultigens is thought to have taken place in the area settled by the Guarani Indians. In the case of the garden bean (Phaseolus vulgaris) the wild original form, Ph. ahorigineus, was discovered some decades ago. Its geographical distribution reaches from northern Argentina through Bolivia, Peru and Colombia to the Andean provinces of Venezuala and it supposedly grows in Central America as well. The area of Ph. ahorigineus is, however, strongly limited in its vertical distribution. The wild bean only occurs in mountain woodland between 1,500 m and 2,700 m. Its natural habitat is the mesothermal alder forest in Argentina and the mist forest region of Colombia and Venezuala. Given a distribution over 5,000 km distance one cannot, even in the case of Phaseolus, talk of a geographically limited 'gene centre' in which domestication is alleged to have taken place. On the basis of these three examples the author has concluded that Vavilov's 'gene centre' theory must be completely rejected. This opinion has been strengthened by personal observations concerning the distribution and evolution of domesticated plants in Africa and Asia. The discussion closes with an appreciation of Vavilov as a person and as an important organiser of Soviet plant breeding and fearless fighter against Lysenkoism. His historic importance for the 'Saving the Gene Pool Programme' is particularly underlined.